Applied cryptography and network security : 13th International Conference, ACNS 2015, New York, NY, USA, June 2-5, 2015, revised selected papers /: 13th International Conference, ACNS 2015, New York, NY, USA, June 2-5, 2015, revised selected papers. (2015) - Unknown
No abstract available